PENYEBAB TERJADINYA SUBSTANDARD PRACTICE BERDASARKAN TEORI LOSS CAUSATION MODEL PADA PENGELAS DI PT BANGUN SARANA BAJA - Dimas Trianggoro Wicaksono (The Indonesian Journal of Occupational Safety and Health, 2017)
Welder had important role for steel fabrication industry, otherwise the job of welder had a variously dangerous potential. The occurring of substandard practice could be prevent by identified the cause of substandard practice. The aim of this research was to study the cause of the occurring of substandard practice on welder at PT. Bangun Sarana Baja. This research was done by using cross sectional design and qualitative approach in order to describe the cause of the occurring of substandard practice on welder at PT. Bangun Sarana Baja Gresik. The respondent of this research was 20 peoples who was work as a welder at PT. Bangun Sarana Baja. The result of this research represent that 80% of welder at PT. Bangun Sarana Baja had performed standard practice. Management has given a lot of variously programs. Personal factor and job factor most of welder supported the occurring of standard practice. The conclusion of this research was most of welder at PT. Bangun Sarana Baja has performed standard practice. Substandard practice occurred because the lack of welder participation in training and the lack of experience before they worked at PT. Bangun Sarana Baja as the personal factor, the difficulty of PPE arrangement, the careless of used PPE, work not based on SOP as the job factor, and lack of control of management on compliance to make standard for each program. Keywords: substandard practice, personal factor, job factor, lack of control of management